2017
DOI: 10.7149/opa.50.2.49018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental micrometer-displacement measurements based on optical vortices

Abstract: ABSTRACT:In this work, a system for measuring micrometer-displacements based on the characteristics of optical vortices is presented. In the proposal, a binary vortex-producing lens (BVPL) programmed to generate optimized optical vortices is transversally displaced from the optical axis, inducing perturbations on the optical characteristics of the vortices that are used as transduction parameters. Specifically, the method proposed theoretically by Anzolin et al. [18], which is based on the asymmetry of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…results in Ref. [19], for an off-axis Gaussian beam impinging onto a binary VPL, agrees with the results presented by Anzolin et al…”
Section: Irradiance Distributionsupporting
confidence: 91%
See 1 more Smart Citation
“…results in Ref. [19], for an off-axis Gaussian beam impinging onto a binary VPL, agrees with the results presented by Anzolin et al…”
Section: Irradiance Distributionsupporting
confidence: 91%
“…They showed that OVs with higher topological charges tend to lose their irradiance symmetry faster than those of lower charges, meaning that higher topological charges are more sensitive to misalignments. This behavior was experimentally verified using binary VPLs [19]. Binary or discretized phase masks differ from the one proposed by Anzolin et al in that they produce multifocal arrangements with multiple OVs [22,23,25,26].…”
Section: Introductionmentioning
confidence: 63%